2013
DOI: 10.1128/jvi.02827-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an HIV-1 Clade A Envelope That Exhibits Broad Antigenicity and Neutralization Sensitivity and Elicits Antibodies Targeting Three Distinct Epitopes

Abstract: f ; Ragon Institute of MGH, MIT, and Harvard, Cambridge, Massachusetts, USA g Broadly neutralizing antibodies (bNAbs) PG9 and PG16 were isolated from an International AIDS Vaccine Initiative (IAVI) Protocol G subject infected with human immunodeficiency virus type 1 (HIV-1) clade A. Both antibodies are highly potent and neutralize greater than 70% of viruses tested. We sought to begin immunogen design based on viral sequences from this patient; however, pseudoviruses prepared with 19 envelope sequences from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 63 publications
2
54
0
Order By: Relevance
“…PG16 and PGT141-145) appear much more dependent on quaternary interactions in the envelope trimer for binding and may, in the case of PG16, also depend on sialylated glycans at Asn-156 and sequences outside of the V1/V2 domain for binding (26). Several studies have also reported the binding of PG9 and PG9-like antibodies to monomeric gp120s and/or V1/V2 scaffolds from selected strains of HIV-1 (22,25,30,54,(63)(64)(65)82). In this regard, the ability to bind one PG9-like antibody does not predict the ability to bind other PG9-like antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…PG16 and PGT141-145) appear much more dependent on quaternary interactions in the envelope trimer for binding and may, in the case of PG16, also depend on sialylated glycans at Asn-156 and sequences outside of the V1/V2 domain for binding (26). Several studies have also reported the binding of PG9 and PG9-like antibodies to monomeric gp120s and/or V1/V2 scaffolds from selected strains of HIV-1 (22,25,30,54,(63)(64)(65)82). In this regard, the ability to bind one PG9-like antibody does not predict the ability to bind other PG9-like antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of a week-6 clone is the basis of the BG505 SOSIP.664 protein construct, in which a T332N substitution was made to restore bNAb epitopes that require the N332 glycan (79, 24). The same change was made to create the BG505.T332N variant of the week-6 BG505 virus (9).…”
Section: Methodsmentioning
confidence: 99%
“…Antisera from cyclically permuted gp120 trimers show higher binding to the CD4 binding site focused outer domain immunogens than antisera from JRFL gp20 and JRFLgp120-L6-hCMP. gp120 binding titers (45,56,57) when a DNA prime-protein boost strategy was adopted.…”
Section: Discussionmentioning
confidence: 99%